Penerapan Model Pembelajaran Tipe Pair Check Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Matematika Pada Materi Bilangan Desimal Kelas IV SD - Veronika Simanjorang; Ester J. Simarmata; Dyan Wulan Sari HS; Juliana Juliana; Saut Mahulae (Departement of Mathematics Education, 2023)
This study aims to improve student learning outcomes in mathematics learning on decimal number material in grade IV SD by applying the pair check type learning model. Based on the data obtained, the increase in pre-test results the average value is 48%, in cycle I there is an average value of 65%, and in cycle II there is an average value of 82%. So it can be concluded that learning by using the Pair Check Type Cooperative Learning model on Decimal Numbers material can improve student learning outcomes. Classically, it can be seen that there is an increase in students' classical learning outcomes. In the pre-test, the learning result was 32%, in cycle I 54%, while in cycle II 75%. This shows that the expected classical learning completeness has been achieved. From the discussion that has been obtained by researchers, there is an increase in good learning outcomes from cycle I and cycle II. This research is said to be successful if the completeness of student learning outcomes classically reaches 75% of students who reach KKM 70 and in cycle II obtained 75% classical learning outcomes. So it can be concluded that through the findings obtained by researchers can provide answers to the previously stated action hypothesis that by applying the Pair Check Type Cooperative model in Mathematics lessons can improve student learning outcomes in the material of Decimal Numbers at St. Thomas 2 Elementary School Medan Learning Year 2022/2023.